In-silico analysis of potential phytochemicals targeting mitogen activating protein kinase-14 (MAPK14) gene in colorectal cancer - Meerab Khalid; Rana Muhammad Mateen; Mohsin Javed; Muhammad Ali; Mohammed Arif Nadeem Saqab; Rukhsana Parveen; Ahmed Asimov; Safura Bibi; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Salah Knani; et al. (Scientific Reports)
Abstract A significant percentage of colorectal cancer (CRC) diagnoses are associated with overexpression of the MAPK14 gene MAPK14 gene or p38 MAPK. It is overexpressed in most cases of colorectal cancer (CRC) and is an important factor for tumor development. CRC is among the most common causes of cancer-related deaths globally It is potent to target this gene for therapeutic intervention because it is important for tumor immune evasion, cell proliferation, survival, and resistance to therapy. By developing treatment techniques that target MAPK14 is a promising approach. In this study, we employed in silico methods to evaluate the potential of phytochemicals as inhibitors of MAPK14, which is overexpressed in CRC. We also included Fruquintinib, an FDA-approved anticancer drug, as a reference compound for molecular docking with MAPK14. Compounds meeting acceptable ADMET profiles were further analyzed using molecular docking, DFT, and MD simulations to identify potential MAPK14 inhibitors. Compound 1 (CID: 44586092) was discovered in our investigation to be a potential therapy for CRC associated with MAPK14.